Creating play opportunities on the school playground: Educator experiences of the Sydney playground project. (16th December 2019) - Sterman, Julia; Villeneuve, Michelle; Spencer, Grace; Wyver, Shirley; Beetham, Kassia S.; Naughton, Geraldine; Tranter, Paul; Ragen, Jo; Bundy, Anita
Abstract: Introduction: Children with disabilities often experience unsupportive environments that restrict their play opportunities and inclusion on the school playground. This exclusion can perpetuate inequities for children with disabilities, with lifelong implications. The Sydney Playground Project uses a simple, innovative intervention consisting of placing recycled materials on the playground and engaging parents and educators in risk reframing sessions to create increased playground choice, control, independence and inclusion for all children. Methods: The purpose of this study was to learn from participants about the utility of the intervention for promoting choice and control among children with disability on the school playground. Data included evaluative interviews with 27 school staff (teaching assistants, teachers, therapists, school leadership) across five participating schools after completing of the intervention. Analysis was thematic and explored prominent ideas first within schools, and then between schools. Results: Prior to the intervention, participating school staff focused on active supervision to support play and student needs. During the intervention, school staff experienced role shift and confusion as they allowed the children increased independence while using the recycled materials and learned to navigate how much independence to give the children. Children engaged in increased imaginative and social play, and school staff adopted higher expectations of children's capabilities. Conclusion: Interventions such as the Sydney Playground Project that collaboratively shift adult perceptions to focus on the capabilities of children with disabilities and increase the supportiveness of the physical environment have great promise in increasing play choice and inclusion on the school playground.